Yusuf Atılgan Öykülerinde Yabancılaşma - Ankay, Nurcan (My University, 2021)
Modernizmin ortaya çıkıp gelişmesi, bireyinkendisini keşfi ve kendisine karşı mesafe alışıylaözdeştir. Modernlikle anılan bireye dönüş vebireyleşme, yabancılaşma ile birlikte düşünülebilir.Modernleşme bireyin kendisiyle, toplumuyla,doğasıyla arasında mesafe koymasına neden olur. Bumesafe, yabancılaşmayı karşılar.Bireyin bilhassa kendisine yabancılaşması,kendisini keşfetmesiyle ilgilidir. Felsefede,sosyolojide çeşitli karşılıkları olan yabancılaşmanınedebiyata yansıması, bireyin edebiyatta anılmasıylagörülmeye başlar. Birey kendisini keşfettikçe çevresiile arasındaki mesafe somutlaşır. Dolayısıyla bireyyabancılaşmanın öznesi haline gelir. Yabancılaşankarakterlerin kendisinden önceki romanlarda daişlenmesine karşın modern anlatının ilktemsilcilerinden olmasının etkisiyle Yusuf Atılgananlatısı, bireyi anlatma açısından önde gelir. Bunedenle kavram, Türk edebiyatındaki ilk etkingörünürlüğünü Yusuf Atılgan anlatısında bulur.Atılgan’ın kahramanları eksik ve yabancıdırlar.Bu çalışmada öncelikle yabancılaşma kavramıele alınacak, ortaya çıkışı ve edebiyata yansımasıincelenecektir. Yabancılaşma kavramınınedebiyattaki temsiline değinilerek Yusuf Atılgananlatısında öne çıkan karakterler üzerinden bir girişyapılacaktır. Ardından yazarın öykülerinde görülenyabancılaşma izlekleri tasnif edilerekdeğerlendirilecektir. Temaların yoğunluğuna göreyapılan bu tasnif şu şekildedir: toplumayabancılaşma, aileye yabancılaşma, kendineyabancılaşma, mekâna yabancılaşma, cinselyabancılaşma, kültürel yabancılaşma, düzeneyabancılaşma. Ele alınan başlıklarla birlikte Atılganöyküsünde bilhassa birey ve toplum arasında birmesafe olduğu görülecek, bu mesafedeğerlendirilmeye çalışılacaktır.

Modernism appears with the emergence and development of the individual, the discovery of himself, and the distance from himself. Return to individual and individuation can be considered together with alienation which associated with modernity. Modernization causes the individual to distance himself from his own society, from his environment. This distance is alienation. Especially the individual’s alienation from himself is related to self-discovery. The appearance of alienation in literature, which has other equivalents in philosophy and sociology, begins to be seen with the emergence of the individual in literature. With the individual discovers himself, his distance from those around him becomes clear. Therefore, the individual becomes the subject of alienation. Although the alienated characters are also mentioned in the novels before him, Yusuf Atılgan’s narrative comes first in terms of telling the individual, with the effect of being one of the first representatives of the modern narrative. Therefore, the concept finds its first effective visibility in Turkish literature in the narrative of Yusuf Atılgan. The heroes of the Atılgan are incomplete and alien. In this study, first of all, alienation will be discussed as a concept. The emergence of the concept and its reflection on literature will be examined. With reference to the representation of the concept of alienation in literature, an introduction will be made through the prominent characters in the Yusuf Atılgan narrative. Then, the alienation patterns seen in the writer's stories will be classified and evaluated. This classification, made according to the density of themes, is as follows: alienation from society, alienation from family, self-alienation, alienation from space, sexual alienation, cultural alienation, alienation to the system. With the topics discussed, it will be seen that there is a distance between the individual and the society in the story of Atılgan. In the study, this distance will be tried to be evaluated.
Alienation in Yusuf Atılgan’s Stories